Radiographic osteoarthritis and pain are independent predictors of knee cartilage loss: a prospective study - Saunders, J.; Ding, C.; Cicuttini, F.; Jones, G. (Internal medicine journal, 2012)
Background:  There is controversy about whether pain and radiographic osteoarthritis (ROA) predict subsequent cartilage loss. The aim of this study was to describe the relationship between ROA, pain and cartilage loss in the knee. Methods:  We studied randomly selected subjects at baseline and approximately 2.9 years later (n= 399). The presence of ROA was assessed at baseline with a standing anteroposterior semiflexed radiograph scored using the Osteoarthritis Research Society International atlas for osteophytes (OP) and joint space narrowing (JSN). Pain was assessed by the Western Ontario McMaster Osteoarthritis Index. Subjects' medial and lateral tibial cartilage volumes were determined by magnetic resonance imaging at both time points. Results:  In cross‐sectional analysis, both medial and lateral tibial cartilage volumes were lower in those with ROA. Any medial ROA predicted medial tibial cartilage loss (3.2% (standard deviation (SD) 5.6) vs 1.9% (SD 5.3) per annum) while any lateral ROA predicted both medial (4.0% (SD 6.0) vs 2.2% (SD 5.3) per annum) and lateral (3.5% (SD 5.8) vs 1.6% (SD 4.2) per annum) tibial cartilage loss (all P < 0.05). In multivariate analysis, JSN and OP at both medial and lateral sites had independent dose–response associations with tibial cartilage loss at both sites. Pain was an independent predictor of lateral, but not medial, tibial cartilage loss after taking ROA into account. Conclusions:  Subjects with ROA (either JSN or OP) and, to a lesser extent, pain lose cartilage faster than subjects without ROA and the more severe the ROA the greater the rate of loss. These findings have implications for the design of clinical trials.